Non-governmental development organisations' sustainability, partnership, and resourcing: futuristic reflections on a problematic trialogue. Issue 5 (3rd July 2016) - Fowler, Alan
ABSTRACT: The CIVICUS Civil Society Index Report 2011 highlights a disassociation between non-governmental development organisations (NGDOs) and the general population. The vulnerability of aided development CSOs is systemic. This can often be traced to a failed trialogue between NGDOs, their partners, and resource providers. This article argues that NGDOs share co-responsibility for their sustainability predicament. Signs of aid uncertainty in the last decades of the millennium were not heeded, nor strategies developed for life beyond aid. Instead, NGDOs were saved by the advent of, and prescribed roles in reaching, the Millennium Development Goals. A repeat performance with the new Sustainable Development Goals is unlikely.